OS7.5 Healthcare utilization, medication use, and productivity loss in glioma patients with depressive symptoms and their family caregivers. (6th September 2019) - Boele, F W; Jansen, F; Meads, D; Verdonck-de Leeuw, I M; Heimans, J J; Reijneveld, J C; Short, S C; Klein, M
Abstract: BACKGROUND: Gliomas are associated with great societal burden through both direct (health and social care) and indirect (e.g., productivity loss) costs, but socioeconomic reports are scarce. We describe costs in a sample of glioma patients at high risk for depression and their family caregivers, and explore relationships between costs and treatable symptoms (depression; fatigue; cognitive complaints). MATERIAL AND METHODS: Data from a nationwide randomised trial comparing internet-based therapy for depressive symptoms with waitlist controls were used. Healthcare utilization, medication use, and productivity loss based on the Trimbos/iMTA questionnaire for Costs associated with Psychiatric Illness (TIC-P) were described and costs in the past 4 weeks were calculated. Caregivers reported on their own costs and wellbeing We used generalized linear regression models to predict costs using multiple observations per participant and robust standard errors. We included depressive symptoms (CES-D), fatigue (CIS), cognitive complaints (MOS), tumour grade (low-/high-grade), and disease status (stable/progression/active treatment). RESULTS: Data from 91 glioma patients and 46 caregivers were used with multiple assessments from baseline through 12 months follow-up. Baseline data showed that over a 4 week period, 64.8% of patients ( M =€394.99, sd =856.83) and 41.3% of caregivers ( M =€131.11, sd =392.89) had used healthcare services. Medication was used by 90.1% of patients ( M =€100.83, sd =191.07) and 43.5% of caregivers ( M =€13.19, sd =21.03). Productivity loss resulted in M =€1231.19, sd =2185.35 for patients and M =€310.92, sd =841.36 for caregivers. In total, mean direct and indirect costs were €1632.22 ( sd =2314.25) for patients and €447.85 ( sd =1002.94) for caregivers. In patients, more depressive symptoms and cognitive complaints were associated with increased healthcare use costs; higher tumour grade and active disease were linked with higher medication costs (all p <.05). Active treatment was related to higher overall costs ( p <.05). In caregivers, increased caregiver fatigue was associated with higher productivity loss and overall costs; more caregiver cognitive complaints were associated with higher total costs; higher tumour grade was associated with higher healthcare use and total costs; and patient active treatment was linked with higher healthcare use costs (all p <.05). CONCLUSION: Direct and indirect costs are substantial in glioma patients and caregivers. This indicates that the true cost of brain tumours is a burden shared between patients, caregivers, the healthcare system, and society more widely. Tentative links between costs and symptoms of depression, fatigue, and cognitive complaints indicate that adequate support may lead to cost reductions. Multivariable regression models are currently being prepared.